Effectiveness of the manual technique of cataract surgery with small incision in a private health facility - Pérez-Martinot, Manuel (2020)
Objective: To determine the effectiveness of the manual technique of cataract surgery with small incision (MSICS) considering visual acuity, postoperative astigmatism, perioperative complications and improvement of the quality of life of patients based on vision. Methods: Observational, descriptive, cross-sectional study in patients operated on cataract with MSICS, between November 2, 2009 and April 30, 2010 in a private ophthalmological center in Lima. Demographic and socioeconomic characteristics, visual acuity (VA), perioperative complications, pre and postoperative astigmatism and quality of life based on vision (CVFV) are included. Results: 806 surgeries were performed in 591 patients. The mean age was 75 years, 304 cases (51.49%) were female and 501 (84.74%) from Metropolitan Lima. The VA without correction at discharge was 20/40 or better in 481 (59.64%) cases, with surgically induced astigmatism less than 2.00 D in 732 (90.80%). Intraoperative complications occurred in 64 cases (7.94%) and postoperative complications in 52 (6.45%). The patient’s CVFV perception based on vision at 30 days was “Good” in 311 (41.25%), “Very Good” in 405 (53.71%) with significant difference (p <0.05) in relation to the preoperative evaluation. Conclusions: The MSICS is a highly effective surgical technique considering good visual acuity and low postoperative induced astigmatism, low percentage of complications and significant improvement of the patient’s CVFV.